Mechanisms and Causes of Osteoporotic Hip Fractures in Elderly Patients - Ayhan Ulusoy; Serdar Demiröz (Galenos Yayinevi, 2020)
Objective:To investigate the causes and occurrence mechanisms of osteoporotic hip fractures in elderly patients in Turkish society.Materials and Methods:This study included 83 consecutive patients who were operated in our clinic due to hip fractures in 2013-2014. The demographic characteristics of the patients, causes and types of fracture, occurrence mechanisms, and location of the fracture, as well as whether the patients lived alone and whether they used walking support were recorded. This information was evaluated retrospectively and analyzed by comparison according to the sex.Results:Ninety-four percent of the patients fell on their right or left side hip joint, and 74% of them fell due to balance disturbances, without any contributing environmental factors. Eighty percent of the patients were injured at home and 56% of them used walking assistance. Only 18% of the patients lived at home alone. According to the Body Mass index only 3% of the patients were obese or overweight, while 49% were underweight.Conclusion:Most patients with hip fracture over the age of 75 are low weight and living with caregivers. Most fractures occur via balance disturbances without any environmental factors and the majority of the patients' fall on one side, not to the front or back. Modifying the patient's clothes and floor materials to reduce the severity of trauma during fall can help reduce the incidence of hip fractures.